A retrospective analysis of recurrent pressure ulcer in a burn center in Northeast China. Issue 4 (November 2019) - Zhang, Nan; Yu, Xin; Shi, Kai; Shang, Fengjia; Hong, Lei; Yu, Jiaao
Abstract: Aim: A retrospective analysis for the pressure ulcer in our burns center in northeast China was taken in order to find the prognostic factors for ulcer recurrence. Materials and methods: We collected the clinical data of hospitalized patients with pressure ulcer ranging from September 2013 to September 2018 involving initial hospitalized data, follow up visit data and recurrent hospitalized data, further univariable and multivariable Cox regression analysis were taken for searching the prognostic factors of recurrent ulcer. Results: The recurrent rate was 8.02%, and in the result of univariable and multivariable Cox regression analysis, blood albumin level on admission below 25 g/dl contributed to the strongest predicting factor for recurrence, with HR = 32.745(95%CI = 8.061–133.022, P  < 0.001). Multiple ulcers showed the second significant importance for predicting recurrence, with HR = 24.226(95%CI = 3.855–152.231, P  = 0.001 < 0.05). Single caregiver contributed to the third prognostic factor, with HR = 0.016(95%CI = 0.004–0.076, P  < 0.001). Conclusion: In a conclusion, multiple ulcers, blood albumin level below 25 g/dl on admission and single caregiver were the three prognostic factors for recurrent pressure ulcer and the shortages of medical care out of hospital in northeast China need more attention urgently. Flap treatment may not be a protective factor for ulcer recurrence, but considered the advantages on the closure of deep wounds, it was still an effective treatment for pressure ulcer nowadays. Highlights: We shared the hospitalization data of pressure ulcer in a burn center in northeast China. Multiple ulcers, albumin level below 25 g/dl and single caregiver were the prognostic factors for recurrent pressure ulcer. Flap treatment was still an effective treatment for pressure ulcer nowadays according to the current study.